Extrapolating Presidential State of the Nation Addresses on Sports and Physical Education: An Analysis Using Voyant Tools - Macapagal, Referson S.; Morante, Venus G.; Tiglao, Leilani P.; Macaspac, Jennelyn D.; Pañosa, Jories Mae A.; Ocampo, Heintjelex C.; Tolentino, Julius Ceazar G.; Miranda, John Paul P. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The study sought to examine the substantive declaration in six Philippine presidents’ State of the Nation Addresses (SONA) from 1987 to 2022 regarding strategic directions and action programs on the future of sports and physical education (SPE). Method – Through text analysis, the researchers selected the terms using quasi-statistics based on the following elements, included in Article IV, Section 19 of the 1987 Philippine Constitution: self-discipline, teamwork, excellence, and a healthy and alert citizenry. Results – As a result, Corazon Aquino’s SONA appears to have the most mentioned words regarding the cited themes and their synonyms based on her speech from 1987 to 1992, at a rate of 90%. However, the state and direction of Philippine SPE were not fully conveyed in most of the Presidents’ SONAs, but they expressed their support through declarations of programs. One of the most remarkable moments in Philippine sports was when President Duterte empowered the National Academy of Sports (NAS) as part of his SONA implications for the development of sports in the country, in which he integrated a customized sports curriculum to support young Filipino players in developing their athletic abilities. Conclusion – Hence, regardless of the Presidents’ SONAs, various themes and the milestones of Philippine sports in each administration since the 1987 Constitution have changed over time. Recommendations – Policy-makers and other stakeholders involved in the promotion of SPE may utilize the implications of the study to establish a comprehensive roadmap anchored on the remarkable accomplishments of previous Philippine presidents that will lay the foundation for a strong future for sports and physical education in the Philippines.